ASSESSMENT OF THE RISK OF DEVELOPING TYPE 2 DIABETES MELLITUS AMONG MEDICAL STUDENTS AT UNIDA-PARAGUAY USING THE FINDRISC SCORE - Assunção e Medeiros, Andreza Thátila; Pedraça, Aline Dos Santos Atherly; dos Santos, Darcy Maria Da Conceição Laura; Nascimento, Patrick Torres; Reyes, Hermin Darío Ayala (Seven Editora, 2026)
Introduction: Type 2 diabetes mellitus (DM2) is a chronic disease with a high prevalence worldwide, whose increasing incidence among young adults is a cause for concern. The objective of this study was to estimate the risk of developing DM2 in UNIDA medical students using the FINDRISC score. Methodology: Non-experimental cross-sectional study with a mixed approach carried out in 2023 with 211 medical students ≥18 years old, excluding pregnant women, individuals with a previous diagnosis of DM2 or cognitive deficit. The FINDRISC questionnaire was applied, cross-culturally adapted for the Paraguayan context. Anthropometric, sociodemographic and health data were collected. Results: The mean age was 30.7 years. The risk of T2DM was classified as: low (47.9%), slightly increased (37.9%), moderate (10.4%), high (3.3%), and very high (0.5%). Factors such as a sedentary lifestyle, inadequate diet, obesity and family history were the main factors associated with the increased risk. Discussion: A study in Cuenca using the FINDRISC method identified a high risk of type 2 diabetes linked to overweight, sedentary lifestyle, and poor diet. Factors such as dyslipidemia, hypertension and obesity are also associated. FINDRISC is an effective, low-cost tool for preventing disease, especially in low-resource populations. In college students, stress and habits such as smoking and poor diet increase the risk of developing diabetes. Conclusion: A significant percentage of students had a moderate to very high risk of developing T2DM, indicating the need for lifestyle-focused preventive interventions.